(untitled) (Research, Society and Development, 2020)
This paper presents a proposal for a teaching and learning method called the Flipped Classroom Cycle Matrix in Higher Education, developed from the flipped classroom educational approach, an active methodological variant of b-learning education. The method is an academic contribution resulting from a Ph.D. research carried out with students (n = 152) from higher education courses in the area of Computer Science, within the Higher Education of Portugal. The investigation of qualitative and quantitative characteristics aimed to investigate the efficiency and effectiveness potential of the inverted classroom methodology regarding the teaching and learning process, within the specific context of Higher Education. An analysis of the research results provided a wealth of information, which broadly showed the students in the study sample, which allowed them to have a strong interest for teaching and learning processes involving digital or b-learning environments and the execution of active techniques of teaching in the classroom. However, students demonstrated difficulties in adapting to the protagonism required in the context of self-directed study, one of the essential characteristics of the flipped classroom methodology. As information displayed through an investigation conducted with higher education students, together with that produced by the scientific literature on the flipped classroom methodology, it is possible to develop and propose this method.